Currency Bands, Target Zones, and Cash Limits : Thresholds for Monetary and Fiscal Policy - Miller, Marcus (IMF Working Papers; Working Paper ;, 1990)
Exchange rate behavior is analyzed in the context of a stochastic rational expectations model in which there are random shocks to the price setting mechanism and in which the authorities choose to impose either nominal or real exchange rate bands. Results are compared to those which emerge from a simple monetary model subject to velocity shocks. The effects of a realignment of the Band, and of fiscal policy used in conjunction with monetary policy to defend the band, are also examined.